WEBSITE PENCARIAN OBJEK WISATA TERBANYAK MENGGUNAKAN METODE DIJKSTRA GIS (STUDI KASUS : OBJEK WISATA DI KABUPATEN KEDIRI) - Kristianto, Hery; Ahmad Heru, Mujianto (Journal of Computer Science and Technology (JCS-TECH), 2026)
Kediri Regency, located in East Java Province, Indonesia, has various tourism destinations with considerable visitor potential. Based on tourism data during the 2019 Eid holiday season, the number of visitors to several tourist destinations in Kediri Regency reached approximately 20,000 visitors. This condition highlights the importance of providing an information system that can assist the public in obtaining tourism information effectively and efficiently. This study aims to develop a tourism object search website for Kediri Regency that provides information on accessible tourist destinations within a certain travel range. The system applies a Geographic Information System (GIS) integrated with the Dijkstra algorithm to determine the shortest route to tourist destinations by utilizing Google Maps Services for location mapping. The implementation was developed as a web-based application using PHP with a native framework. The results show that the implementation of the GIS-based Dijkstra algorithm improves the effectiveness of tourism location data management through the use of latitude and longitude coordinates stored in a database, while also generating the shortest route recommendations from the center of Kediri City, namely Kediri Town Square, to tourist destinations in Kediri Regency in an optimal manner. Keywords: Attraction search, Web, Dijkstra, GIS, Google Maps Services